TRANSITION METAL COMPLEXES MEDIATED EFFICIENT AND FACILE CLEAVAGE OF OXIMES AND PHENYLHYDRAZONE TO CARBONYL COMPOUNDS - Mohammed, Tasneem; ARIFUDDIN M; Al-arifi, Mohamed N; Syed Wajid (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Â  Graphical Abstract Purpose: To report a new and efficient method for the regeneration of carbonyl compounds from their oximes and phenylhydrazones by employing transition metal complexes under mild conditions. Methods: Different oxime and phenylhydrazone complexes have been examined for this regeneration process and found effective. Results: A new method for the cleavage of oximes and phenylhydrazone into their corresponding carbonyl compounds has been done successfully. Conclusion: The present method is of practical significance as it is rapid, high yielding, involves simple work-up under the very mild condition, and it applicable to both aldehydes and ketones. Thus, it is believed that the present method appears to be viable alternative to existing procedures. Keywords: Regeneration, Carbonyl compounds, Oximes, Phenylhydrazones, Transition metal complexes.